The Validity of Body Composition Measurement Using Dual Energy X-Ray Absorptiometry for Estimating Resting Energy Expenditure - Usui, Chiyoko; Taguchi, Motoko; Ishikawa-Takata, Kazuko; Higuchi, Mitsuru (IntechOpen, 2012)
None